2016
DOI: 10.3892/or.2016.5188
|View full text |Cite
|
Sign up to set email alerts
|

Gambogenic acid induces proteasomal degradation of CIP2A and sensitizes hepatocellular carcinoma to anticancer agents

Abstract: Cancerous inhibitor of protein phosphatase 2A (CIP2A) is an oncoprotein that is overexpressed in many human malignancies. It regulates phosphorylated AKT and stabilizes c‑Myc in cell proliferation and tumor formation, suggesting that CIP2A plays an essential role in the development of cancer. In the present study, we report that a natural compound, gambogenic acid (GEA), induced the degradation of CIP2A via the ubiquitin‑proteasome pathway. Interestingly, the combination of GEA and proteasome inhibitors potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…Gambogenic acid (GNA, Figure ), a dry gum resin of the Garcinia genus, is a main anticancer active component derived from traditional Chinese medicine gamboge …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gambogenic acid (GNA, Figure ), a dry gum resin of the Garcinia genus, is a main anticancer active component derived from traditional Chinese medicine gamboge …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed that GNA possess strong antitumour activity to melanoma cells, gastric carcinoma cells, liver cancer cells and other cancer cells . Li et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely proven PP2A is a tumor suppressor since the initial recognition that its inhibitor okadaic acid (OA) is a tumor promoter . However, PP2A is genetically inactivated in many types of cancer while the expression of cancerous inhibitor of PP2A (CIP2A) has been proven in many kinds of malignancy such as human hepatocellular carcinoma (HCC), colon cancer, and cervical cancer . HCC remains a major health problem and ranks the fifth most common cancer around the world.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, PP2A is genetically inactivated in many types of cancer while the expression of cancerous inhibitor of PP2A (CIP2A) has been proven in many kinds of malignancy such as human hepatocellular carcinoma (HCC), colon cancer, and cervical cancer. [4][5][6] HCC remains a major health problem and ranks the fifth most common cancer around the world. Currently, the treatment of the cancer is not satisfactory, and the discovery of new therapeutic agents is in demand.…”
mentioning
confidence: 99%